Experiences of educational use of technologies a case of facebook, google plus and the use of blogs - Kennedy-Russell, Ana (Proceedings - 2016 11th Latin American Conference on Learning Objects and Technology, LACLO, 2016)
This workshop considers to share some experiences of educational practice of technologies used in English courses at the Technological Institute of Costa Rica, known in Spanish by its abbreviation (ITCR) throughout three years. There are three cases chosen using technological tools such as Facebook, Google Plus and the blog. Although courses at the ITCR are face to face, some technological components have been included in our courses so as to assure a transformation process of both professors and students' roles. These experiences will be shared during the Eleventh Latin American Conference on Learning Objects and Technologies (LACLO 2016). Once experiences have been public, the aim will be that of motivating professors to make further research pertaining other technological tools which hopefully will permit our students to improve their abilities and performance in the English language.
Conferencia
Keywords: Educación; Tecnología; Internet; Aprendizaje; Inglés; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education